An assessment of the spontaneous locomotor activity of BALB/c mice - Yusuke Miyazaki; Koji Kobayashi; Seiji Matsushita; Naoyuki Shimizu; Takahisa Murata (Elsevier, 2022)
The surrounding environment affects the behavior of an animal. Therefore, long-term observation of an animal's behavior in its natural breeding environment is an effective approach to predict and understand animal behavior in greater detail. Spontaneous locomotor activity (SLA), the movement of animals in their breeding environment, is one of the most important behavioral indices for experimental animals. We here established an SLA measurement system using image analyses to obtain basic data from BALB/c mice. To record the movement of the mice, we used an infrared video camera. SLA of mice were calculated by detecting their geometric center in each frame. This system could detect the mouse correctly more than 99.999% in all frames. Further, we investigated the effects of habituation, age, and sex on the SLA of BALB/c mice. Three days of habituation were required to decrease the SLA of mice placed in novel cages. The 16- and 32-week-old mice were less active than 4-week-old mice. No significant differences were detected between males and females. We also found that BALB/c and C57BL/6 mice differed in their active and resting rhythms. In conclusion, we developed an SLA measurement system and obtained basic SLA data from BALB/c mice.